Artichoke Polyphenols Produce Skin Anti-Age Effects by Improving Endothelial Cell Integrity and Functionality - Isabella D’Antuono; Antonietta Carola; Luigi M. Sena; Vito Linsalata; Angela Cardinali; Antonio F. Logrieco; Maria Gabriella Colucci; Fabio Apone (Molecules, 2018)
Artichoke is a characteristic crop of the Mediterranean area, recognized for its nutritional value and therapeutic properties due to the presence of bioactive components such as polyphenols, inulin, vitamins and minerals. Artichoke is mainly consumed after home and/or industrial processing, and the undersized heads, not suitable for the market, can be used for the recovery of bioactive compounds, such as polyphenols, for cosmetic applications. In this paper, the potential skin anti-age effect of a polyphenolic artichoke extract on endothelial cells was investigated. The methodology used was addressed to evaluate the antioxidant and anti-inflammatory activities and the improvement of gene expression of some youth markers. The results showed that the artichoke extract was constituted by 87% of chlorogenic, 3,5-O-dicaffeoylquinic, and 1,5-O-dicaffeoylquinic acids. The extract induced important molecular markers responsible for the microcirculation and vasodilatation of endothelial cells, acted as a potential anti-inflammatory agent, protected the lymphatic vessels from oxidative damage by ROS formation, and enhanced the cellular cohesion by reinforcing the tight junction complex. In addition, the artichoke extract, through the modulation of molecular pathways, improved the expression of genes involved in anti-ageing mechanisms. Finally, clinical testing on human subjects highlighted the enhancement by 19.74% of roughness and 11.45% of elasticity from using an artichoke extract cosmetic formulation compared to placebo cream.